Comparison of the Automated cobas u 701 Urine Microscopy and UF‐1000i Flow Cytometry Systems and Manual Microscopy in the Examination of Urine Sediments. Issue 5 (3rd February 2016) - Lee, Wonmok; Ha, Jung‐Sook; Ryoo, Nam‐Hee
Abstract : Background: The cobas u 701, a new automated image‐based urine sediment analyzer, was introduced recently. In this study, we compared its performance with that of UF‐1000i flow cytometry and manual microscopy in the examination of urine sediments. Methods: Precision, linearity, and carry‐over were determined for the two urine sediment analyzers. For a comparison of the method, 300 urine samples were examined by the automated analyzers and by manual microscopy using a KOVA chamber. Results: Within‐run coefficients of variation (CVs) for the control materials were 7.0–8.8% and 1.7–5.7% for the cobas u 701 and UF‐1000i systems, respectively. Between‐run CVs were 8.5–9.8% and 2.7–5.4%, respectively. Both instruments showed good linearity and negligible carry‐over. For red blood cells (RBC), white blood cells (WBC), and epithelial cells (EPI), the overall concordance rates within one grade of difference among the three methods were good (78.6–86.0%, 88.7–93.8%, and 81.3–90.7%, respectively). The concordance rate for casts was poor (66.5–68.9%). Conclusion: Compared with manual microscopy, the two automated sediment analyzers tested in this study showed satisfactory analytical performances for RBC, WBC, and EPI. However, for other urine sediment particles confirmation by visual microscopy is still required.